2018
DOI: 10.1080/09540121.2018.1515471
|View full text |Cite
|
Sign up to set email alerts
|

HIV care engagement and ART adherence among Kenyan gay, bisexual, and other men who have sex with men: a multi-level model informed by qualitative research

Abstract: Gay, bisexual, and other men who have sex with men (GBMSM) are highly stigmatized and male–male sex is often criminalized in sub-Saharan Africa, impeding access to quality care for sexual health, HIV prevention, and treatment. To better understand HIV care engagement and antiretroviral therapy (ART) adherence among GBMSM in this context, a conceptual model incorporating sociocultural factors is needed. We conducted a qualitative study of barriers to and facilitators of HIV care engagement and ART adherence amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
38
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 23 publications
(26 reference statements)
9
38
0
1
Order By: Relevance
“…We found that stigma constrained participation in crowdsourcing contests. This finding is consistent with prior research which found HIV-related stigma negatively impacts community engagement in HIV research [35][36][37]. Stigma associated with discussing HIV in public settings was closely connected to broader social inequalities of gender, sexuality, and class.…”
Section: Discussionsupporting
confidence: 90%
“…We found that stigma constrained participation in crowdsourcing contests. This finding is consistent with prior research which found HIV-related stigma negatively impacts community engagement in HIV research [35][36][37]. Stigma associated with discussing HIV in public settings was closely connected to broader social inequalities of gender, sexuality, and class.…”
Section: Discussionsupporting
confidence: 90%
“…This study revealed that 36.5% of the participants ever had sex with women. It was close to similar studies from China, with a proportion between 27% and 56%, but it was higher than a similar study in the USA, which showed 20% of the participants ever had sex with female partners 5,2932 . Apart from 20.1% of the study participants were self-reported bisexuality, another explanation could not be excluded.…”
Section: Discussionsupporting
confidence: 80%
“…Facilitators to health service access In Kenya, Graham and colleagues found that identifying providers and family or friends as well as engaging with trusted LGBTI organisations, assisted many men with accepting and disclosing their sexual identity. 32 Our findings also highlighted the importance of providerpatient trust in health service utilisation and the role that training in gender diversity can have in building trusting relationships.…”
Section: Engagement In Health Servicesmentioning
confidence: 58%
“…Findings from studies in other African countries (Kenya, Botswana, Namibia, Malawi, South Africa and Swaziland) show the disproportionate burden of HIV and the influence of stigma on health seeking behaviour. [32][33][34][35][36] As has been discussed, since early in the HIV epidemic, stigmatisation of marginalised populations influences healthcare utilisation in a myriad of ways, including fear of seeking healthcare, lack of disclosure of same sex relationships to healthcare providers, denial of services related to one's sexuality. 33 A global online survey of over 4000 participants evaluated the effect of the enforcement of laws criminalising homosexuality on access to services and found that arrests and convictions under laws applicable to being MSM had a strong negative association with use of HIV prevention and care services with the strongest effects in sub-Saharan Africa.…”
Section: Engagement In Health Servicesmentioning
confidence: 99%